Desain Alat Pembersih Panel Surya Otomatis - Jahirwan Ut Jasron; Yasoni Eliaser Seran; Ben V Tarigan (LONTAR Jurnal Teknik Mesin Undana (LJTMU ), 2025)
Solar energy is one type of energy utilized, especially for solar panels. Solar panels can convert solar energy into electrical energy. Solar panels, as an alternative source of electrical energy, can be utilized by people who need electrical energy. This research aims to determine the output power produced by solar panels that have not been cleaned and have been cleaned using an automatic solar panel cleaning tool from the difference in motor rotation variations, namely 11 rpm, 27 rpm, and 330 rpm. This research shows that the output power of solar panels that have yet to be cleaned on the first day produces a power of 56.3. In contrast, the output power of solar panels that have been cleaned produces a power of 103.1, and on the second day, the output power produced by solar panels that have not been cleaned. Cleaned was 71.3, and the power of solar panels that had been cleaned produced a power of 97.1. Then, on the third day, the power produced by solar panels that had not been cleaned was 65.5, and the power of solar panels that had been cleaned produced power of 78,6.